Guidelines for Preventing the Transmission of Mycobacterium tuberculosis in Health-Care settings, 2005. - Jensen PA; Lambert LA; Iademarco MF; Ridzon R (MMWR: Morbidity & Mortality Weekly Report, 2006)
In 1994, CDC published the Guidelines for Preventing the Transmission of Mycobacterium tuberculosis in HealthCare Facilities, 1994. The guidelines were issued in response to 1) a resurgence of tuberculosis (TB) disease that occurred in the United States in the mid-1980s and early 1990s, 2) the documentation of several high-profile health-care--associated (previously termed 'nosocomial') outbreaks related to an increase in the prevalence of TB disease and human immunodeficiency virus (HIV) coinfection, 3) lapses in infectioncontrol practices, 4) delays in the diagnosis and treatment of persons with infectious TB disease, and 5) the appearance and transmission of multidrug-resistant (MDR) TB strains. The 1994 guidelines, which followed statements issued in 1982 and 1990, presented recommendations for TBinfection control based on a risk assessment process that classified health-care facilities according to categories of TB risk, with a corresponding series of administrative, environmental, and respiratoryprotection control measures.The TB infectioncontrol measures recommended by CDC in 1994 were implemented widely in health-care facilities in the United States. The result has been a decrease in the number of TB outbreaks in health-care settings reported to CDC and a reduction in health-care--associated transmission of Mycobacterium tuberculosis to patients and health-care workers (HCWs). Concurrent with this success, mobilization of the nation's TBcontrol programs succeeded in reversing the upsurge in reported cases of TB disease, and case rates have declined in the subsequent 10 years. Findings indicate that although the 2004 TB rate was the lowest recorded in the United States since national reporting began in 1953, the declines in rates for 2003 (2.3%) and 2004 (3.2%) were the smallest since 1993. In addition, TB infection rates greater than the U.S. average continue to be reported in certain racial/ethnic populations. The threat of MDR TB is decreasing, and the transmission of M. tuberculosis in health-care settings continues to decrease because of implementation of infection-control measures and reductions in community rates of TB.Given the changes in epidemiology and a request by the Advisory Council for the Elimination of Tuberculosis (ACET) for review and update of the 1994 TB infectioncontrol document, CDC has reassessed the TB infectioncontrol guidelines for health-care settings. This report updates TB control recommendations reflecting shifts in the epidemiology of TB, advances in scientific understanding, and changes in health-care practice that have occurred in the United States during the preceding decade. In the context of diminished risk for health-care--associated transmission of M. tuberculosis, this document places emphasis on actions to maintain momentum and expertise needed to avert another TB resurgence and to eliminate the lingering threat to HCWs, which is mainly from patients or others with unsuspected and undiagnosed infectious TB disease. CDC prepared the current guidelines in consultation with experts in TB, infection control, environmental control, respiratory protection, and occupational health. The new guidelines have been expanded to address a broader concept; health-care--associated settings go beyond the previously defined facilities. The term 'health-care setting' includes many types, such as inpatient settings, outpatient settings, TB clinics, settings in correctional facilities in which health care is delivered, settings in which home-based health-care and emergency medical services are provided, and laboratories handling clinical specimens that might contain M. tuberculosis. The term 'setting' has been chosen over the term 'facility,' used in the previous guidelines, to broaden the potential places for which these guidelines apply.